1973
DOI: 10.1071/bi9730077
|View full text |Cite
|
Sign up to set email alerts
|

Stress Metabolism IV. The Influence of (2-Chloroethyl)Trimethylammonium Chloride and Gibberellic Acid on the Growth and Proline Accumulation of Wheat Plants During Water Stress

Abstract: Wheat plants (cv. Gabo) were grown in nutrient solution and supplied with (2- chloroethyl)trimethylammonium chloride (CCC) in the rooting medium 1 week after germination. Ten days later the plants were subjected to water stress by substituting polyethylene glycol solution (mol. wt. 4(00) for the nutrient solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1974
1974
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 14 publications
(22 reference statements)
0
2
0
1
Order By: Relevance
“…After re-watering, the proline content of the rice varieties decreased rapidly, reaching values similar to those under the control condition (Figure 4). Several studies have indicated that proline accumulated during episodes of water deficit is lost rapidly when the water deficit is eliminated (Blum & Ebercon, 1976;Singh et al, 1973;Stewart, 1972). Once osmotic stress is withdrawn, proline is oxidised into Δ 1 -pyrroline-5-carboxylate (P5C) by proline dehydrogenase, also known as proline oxidase, the first enzyme in the proline degradation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…After re-watering, the proline content of the rice varieties decreased rapidly, reaching values similar to those under the control condition (Figure 4). Several studies have indicated that proline accumulated during episodes of water deficit is lost rapidly when the water deficit is eliminated (Blum & Ebercon, 1976;Singh et al, 1973;Stewart, 1972). Once osmotic stress is withdrawn, proline is oxidised into Δ 1 -pyrroline-5-carboxylate (P5C) by proline dehydrogenase, also known as proline oxidase, the first enzyme in the proline degradation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Also, as proline content increased, photosynthetic efficiency significantly decreased, likely due to the decrease in stomatal conductance that increases the accumulation of ABA content. Several studies have shown that proline accumulates in dehydrated conditions and is rapidly lost when dehydration conditions are relieved ( Blum & Ebercon, 1976 ; Singh, Aspinall & Paleg, 1973 ; Stewart, 1972 ). When osmotic stress is removed, proline is oxidized to Δ1-pyrroline-5-carboxylate (P5C) by proline dehydrogenase, also known as proline oxidase, the first enzyme in the proline degradation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…HSIAO 1973). Neben diesen Wirkungen der ABA auf Stornata und Permeabili tät von Membranen sind mit dem Anstieg der ABA in vielen gestreßten Pflan zen aber auch, lange Zeit wenig beachtete, metabolische Veränderungen ver bunden, von denen die starke Zunahme des freien Prolins am bemerkenswerte sten ist, die in vielen gestreßten Pflanzen beobachtet werden kann (BARNETT und NAYLOR 1966, SINGH et al 1973a, b, ASPINALL et al 1973, HUBER 1974 u.a.). Dieser Prolinanstieg kann auch durch exogene Behandlung der Pflanzen mit ABA hervorgerufen werden (HUBER 1974, ASPINALL et al 1973.…”
unclassified